The harmful acute effects of clomipramine in the rat liver: Impairments in mitochondrial bioenergetics - Bizerra, Paulo Francisco Veiga; Itou da Silva, Fernanda Sayuri; Gilglioni, Eduardo Hideo; Nanami, Letícia Fernanda; Klosowski, Eduardo Makiyama; de Souza, Byanca Thais Lima; Raimundo, Ana Flávia Gatto; dos Santos, Karina Borba Paulino; Mewes, Juliana Moraes; Constantin, Renato Polimeni; Mito, Márcio Shigueaki; Ishii-Iwamoto, Emy Luiza; et al. (Elsevier, 2023)
Clomipramine, a tricyclic antidepressant used to treat depression and obsessive-compulsive disorder, has been linked to a few cases of acute hepatotoxicity. It is also recognized as a compound that hinders the functioning of mitochondria. Hence, the effects of clomipramine on mitochondria should endanger processes that are somewhat connected to energy metabolism in the liver. For this reason, the primary aim of this study was to examine how the effects of clomipramine on mitochondrial functions manifest in the intact liver. For this purpose, we used the isolated perfused rat liver, but also isolated hepatocytes and isolated mitochondria as experimental systems. According to the findings, clomipramine harmed metabolic processes and the cellular structure of the liver, especially the membrane structure. The considerable decrease in oxygen consumption in perfused livers strongly suggested that the mechanism of clomipramine toxicity involves the disruption of mitochondrial functions. Coherently, it could be observed that clomipramine inhibited both gluconeogenesis and ureagenesis, two processes that rely on ATP production within the mitochondria. Half-maximal inhibitory concentrations for gluconeogenesis and ureagenesis ranged from 36.87 μM to 59.64 μM. The levels of ATP as well as the ATP/ADP and ATP/AMP ratios were reduced, but distinctly, between the livers of fasted and fed rats. The results obtained from experiments conducted on isolated hepatocytes and isolated mitochondria unambiguously confirmed previous propositions about the effects of clomipramine on mitochondrial functions. These findings revealed at least three distinct mechanisms of action, including uncoupling of oxidative phosphorylation, inhibition of the FoF1-ATP synthase complex, and inhibition of mitochondrial electron flow. The elevation in activity of cytosolic and mitochondrial enzymes detected in the effluent perfusate from perfused livers, coupled with the increase in aminotransferase release and trypan blue uptake observed in isolated hepatocytes, provided further evidence of the hepatotoxicity of clomipramine. It can be concluded that impaired mitochondrial bioenergetics and cellular damage are important factors underlying the hepatotoxicity of clomipramine and that taking excessive amounts of clomipramine can lead to several risks including decreased ATP production, severe hypoglycemia, and potentially fatal outcomes.
Keywords: Cellular structure; Intact liver; Isolated hepatocytes; Isolated mitochondria; Mitochondrial toxicity; Tricyclic antidepressants